Fine‐needle aspiration as an alternative to core needle biopsy for tumour molecular profiling in precision oncology: prospective comparative study of next‐generation sequencing in cancer patients included in the SHIVA02 trial - Dupain, Célia; Masliah‐Planchon, Julien; Gu, Céline; Girard, Elodie; Gestraud, Pierre; Du Rusquec, Pauline; Borcoman, Edith; Bello, Diana; Ricci, Francesco; Hescot, Ségolène; Sablin, Marie‐Paule; Tresca, Patricia; et al. (Molecular oncology, 2021)
High‐throughput DNA analyses in cancers allow the detection of molecular abnormalities that can guide patients' treatment. The collection of a tumour DNA is mainly performed on a biopsy, an invasive procedure for the patients. Another less invasive method consists in using a fine needle. We showed that fine‐needle biopsies are as suitable as a classical biopsy for DNA analysis. High‐throughput molecular profiling of solid tumours using core needle biopsies (CNB) allows the identification of actionable molecular alterations, with around 70% success rate. Although several studies have demonstrated the utility of small biopsy specimens for molecular testing, there remains debate as to the sensitivity of the less invasive fine‐needle aspiration (FNA) compared to CNB to detect molecular alterations. We aimed to prospectively evaluate the potential of FNA to detect such alterations in various tumour types as compared to CNB in cancer patients included in the SHIVA02 trial. An in‐house amplicon‐based targeted sequencing panel (Illumina TSCA 99.3 kb panel covering 87 genes) was used to identify pathogenic variants and gene copy number variations (CNV) in concomitant CNB and FNA samples obtained from 61 patients enrolled in the SHIVA02 trial (NCT03084757). The main tumour types analysed were breast (38%), colon (15%), pancreas (11%), followed by cervix and stomach (7% each). We report 123 molecular alterations (85 variants, 23 amplifications and 15 homozygous deletions) among which 98 (80%) were concordant between CNB and FNA. The remaining discordances were mainly related to deletions status, yet undetected alterations were not exclusively specific to FNA. Comparative analysis of molecular alterations in CNB and FNA showed high concordance in terms of variants as well as CNVs identified. We conclude FNA could therefore be used in routine diagnostics workflow and clinical trials for tumour molecular profiling with the advantages of being minimally invasive and preserve tissue material needed for diagnostic, prognostic or theranostic purposes.